Effects of Church Attendance Vs. Private Religious Activities on Suicidal Ideation: A Study of Rural US College Students - Kim, Yi Jin (Journal of religion and health, 2021)
To examine how religiosity and depression directly/indirectly affect suicidal ideation in White and African American rural college students. The data from 272 rural college students were used to test the moderated mediation model using PROCESS macro. Students with higher church attendance and/or private religious activities had lower depressive symptoms, which in turn significantly alleviated their suicidal ideation. There was no significant racial group difference in the direct/indirect effects. The college students who did not engage in religious meetings and private religious activities were inclined to have depressive symptoms and a higher risk of suicidal ideation.